Domestic violence among Indigenous Women - Barjos, Nursia M. (The Threshold: the Official Research Journal of Jose Rizal Memorial State University, Zamboanga del Norte, 2016)
This qualitative study aimed to document the lived experiences of the Badjao women on domestic violence. To capture the realities of violence, interviews and focus group discussion were conducted. The data gathered were transcribed and processed using thematic analysis. The study revealed that Badjao women looked at themselves as weak, subordinate, submissive and dependent on their husbands. With a patriarchal family value system, it is justifiable for husband to be domineering and abusive. Biases and discriminations were reinforced by gender, insensitive religious interpretations and practices, thus, making Badjao women physically and emotionally abused resulting to low self-esteem, frustration, despair and intense grief. Moreover, most of the victims tended to hide the abuses and just turned to their relatives and friends for assistance; sometimes they would seek spiritual guidance from their religious leader. The issues on violence are amicably settled as the spiritual leader stressed that women must be subservient to their husband. There is public education to avert the escalating domestic violence issues among Badjao women.